(untitled) (Advancements in Homeopathic Research, 2022)
Objective: The study was conducted to elicit the pathogenetic response of Rhus toxicodendron in 30C potency on healthy human volunteers. Methodology: The proving of drug Rhus toxicodendron was conducted in the Department of Homoeopathic Pharmacy, Vinayaka Mission’s Homoeopathic Medical College and Hospital, Salem, through randomized, double-blind, placebo-controlled study. The drug was proved in 30th centesimal potency on 36 apparently healthy volunteers who were selected after conducting pre- trial medical examinations by the medical specialists and routine laboratory investigations. 18 of them were kept on interventional drug trial and remaining, under placebo. As per the proving protocol, 56 dose schedule [i.e., 56 doses of drug/placebo were consumed by a prover in each batch] was followed. The symptoms generated during the trial period were noted by the volunteers and elaborated by the proving masters which were compiled at Homoeopathic drug proving cum data processing unit of the department. Result: Out of 18 provers who were on the interventional drug trial, only 16 manifested symptoms. The drug was able to produce symptoms in 30C potencies. Totally 17 new symptoms have appeared. Conclusion: The drug pathogenesis evolved indicates its therapeutic use for Chilblains, Cough, Dengue fever, Dysentry, Diarrhoea, Enteric fever, Eczema, Gout, Headache, Lumbago, Neuralgia, Paralysis, Restlessness, Rheumatism, Sciatica, Sprains, etc.